Financial Literacy and Digital Innovation on MSMEs Performance Through Business Sustainability at Bulak Fish Center MSMEs in East Surabaya - Kirana, Tri Musthika; Nur, Dhani Ichsanuddin; Bachtiar, Arief (Indonesian Journal of Business Analytics, 2024)
Micro, Small and Medium Enterprises (MSMEs) currently require good financial performance for sustainability and decision making. In the future, MSMEs will only develop in terms of quantity but have not been matched by good quality. For this reason, financial literacy and digital innovation are things that support the performance of MSMEs. Finding out (1) how financial literacy affects MSME performance, (2) how digital innovation affects MSME performance, and (3) how financial literacy affects MSME performance through business sustainability are the goals of this study (4) the influence of digital innovation on MSME performance through business sustainability. The population in this study are all owners and managers of East Surabaya Bulak Fish Center (SIB) MSMEs who run a trading business in food, drinks and souvenir accessories. The study sample consisted of seventy-five individuals who were managers or owners of businesses. Saturated sampling was the method of sampling, and partial least squares (PLS) analysis was the method of analysis. The findings of this study show that (1) financial literacy increases the contribution to the performance of MSMEs, (2) digital innovation increases the contribution to the performance of MSMEs, (3) financial literacy increases the contribution to the performance of MSMEs through business sustainability, (4) digital innovation increases the contribution to MSME performance through business sustainability.